Comparative study of the anti-inflammatory effect and acute toxicity of Sacha Inchi oils (Plukenetia volubilis and Plukenetia huayllabambana) in mice - Aguilar-Olano, Jose Luis; Davila Paico, Silvia; Alvarez, Christian Pitot (Frontiers in Immunology, 2025)
IntroductionThe seed of Sacha Inchi (Plukenetia spp.), a plant native from the Peruvian Amazon, has a high content of Omega 3 (ω-3) in its composition, reaching up to 53% of its total fatty acids. Fatty acids ω-3 can significantly reduce the production of proinflammatory molecules and could therefore inhibit or reduce the inflammatory response.ObjectiveWe evaluate the oils from the seeds of two species of Sacha Inchi: Plukenetia volubilis and Plukenetia huayllabambana for their inflammation inhibitory capacity, in an in vivo and in vitro model in experimental animals.ResultsThe physicochemical analysis showed that Sacha Inchi oil obtained from P. huayllabambana seeds contained 53% ω-3, whereas that obtained from P. volubilis presented 47%. The evaluation of cytotoxicity in culture of normal splenocytes demonstrated that both oils are non-cytotoxic, because they showed a median inhibitory concentration (IC50) of 48,561 mg/mL for P. volubilis and 50,695 mg/mL for P. huayllabambana, which, physiologically, are values impossible to achieve in cells. In the evaluation of acute toxicity (mean lethal dose, LD50) in C57 mice, P. volubilis obtained the value of 63,603 mg/kg, whereas P. huayllabambana obtained 74,638 mg/kg, which classifies both oils in the category of Relatively Harmless, that is, non-toxic for the models tested. Both oils demonstrated a statistically significant anti-inflammatory effect, with P. huayllabambana oil being the most effective, presenting a 62% percentage of inhibition of inflammation. We demonstrate the safety and potential anti-inflammatory activity of Plukenetia sp., which could serve as a basis for future research.